Nuclear Security Education in Nigeria: University of Port Harcourt Approach - Ayode Kuye; Lucky Uyigue (International Journal of Nuclear Security, 2019)
This paper is focused on how the Centre for Nuclear Energy Studies, University of Port Harcourt has been able to pursue its set mandates which include, educating and training Nigerians about nuclear energy as well as conducting research on how to deploy its peaceful applications. To actualize these mandates, it needed to develop competencies and capacities in its focus areas: modeling and simulation of nuclear power plant, thermal hydraulics and nuclear security. It had adopted the method of graded approach in developing its capabilities in nuclear security. This was done through systematic and gradual process, by exposing its academic personnel to professional and curriculum development courses in nuclear security on train-the-trainer basis. The outcomes to date are that the Centre for Nuclear Energy Studies has been able to upgrade the strength of nuclear security in the existing master’s programme in nuclear engineering, commenced the postgraduate certificate programme in nuclear security science, trained over 50 persons both locally and internationally in nuclear security through organized annual workshop and has been able to establish strong collaborations with other institutions within Nigeria and outside.
Keywords: Nuclear Security; Professional development course; curriculum development; National training workshop and graded approach